2016
DOI: 10.2298/gsf1614169p
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal analysis of natural resources degradation in the Likodra River watershed

Abstract: Soil is an important natural resource whose proper use requires a good knowledge of all endogenous and exogenous factors that cause different types of degradation. Erosion is one of the forms of soil degradation. Erosion processes are characterized by a distinctive complexity and the factors affecting them are dynamics and change in space and time. A complex system degradation requires a multidisciplinary approach to the use of modern methods and techniques. Today, a large number of models ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This research is a further development of research aimed at developing methodological principles for improving the efficiency of data processing in special-purpose information systems published earlier [26,27]. Areas of further research should be aimed at reducing computational costs in the processing of various types of data in special-purpose information systems.…”
Section: Discussion Of the Results Of Evaluating The Effectiveness Of A Complex Solution Search Methodsmentioning
confidence: 97%
“…This research is a further development of research aimed at developing methodological principles for improving the efficiency of data processing in special-purpose information systems published earlier [26,27]. Areas of further research should be aimed at reducing computational costs in the processing of various types of data in special-purpose information systems.…”
Section: Discussion Of the Results Of Evaluating The Effectiveness Of A Complex Solution Search Methodsmentioning
confidence: 97%
“…Let`s make the modeling of the complex methodology of processing data of different types in accordance with the algorithms of procedures in Fig. 3-6 and expressions (1)- (3). The technique of processing data of various types in intelligent decision support systems is proposed.…”
Section: Discussion Of the Results Of The Development Of A Comprehensive Methodology For Processing Different Data Typesmentioning
confidence: 99%
“…In the article [3], the analysis of known methods of processing various types of information is carried out. Also, it was found that the researchers identify a number of problems associated with the process of data extraction for further analytical processing:…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In [7], the description of the work of spatial and temporal degradation of soil erosion is carried out. The description of the soil erosion process is described using the method of erosion potential.…”
Section: The Complex Methodology For Processing Heterogeneous Data Inmentioning
confidence: 99%